CERAI GUGAT PERSPEKTIF PERUNDANG-UNDANGAN DI INDONESIA (STUDI KASUS DI PENGADILAN AGAMA KELAS 1B WATAMPONE PADA TAHUN 2010-2012) - Darliana Darliana (Institut Agama Islam Negeri Bone, 2021)
Abstract The results show that the divorce to sue in the Religious Class 1B Watampone from year to year has increased significantly, the events of divorce sue greater in number than the divorce on the grounds that the wife is more aware of their rights and obligations in marriage. Factors that lead to divorce contested in the Religious are factors moral, Hurting, child marriage, dispute continuously, biological defect and no harmony, these factors are supported by a state of